Perancangan Sistem Marketplace B2B IT Asset Disposition dengan Human Centered Design pada Relapify - Rachel Adzkia Zahra; Ryna Parlyna; Osly Usman (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to design and develop a web-based B2B marketplace prototype called ReLapify as a digital solution for IT Asset Disposition (ITAD) management and transactions in Indonesia. The research addresses several issues, including inefficiencies in IT asset management, information asymmetry in B2B transactions, limited transaction security and legal certainty, and the absence of environmental impact reporting to support corporate ESG implementation. The system was developed using the Waterfall method, consisting of requirements analysis, system design, implementation, testing, deployment, and documentation stages. A Human-Centered Design (HCD) approach based on ISO 9241-210:2019 was applied to ensure that the platform met user needs. The platform was developed using Lovable AI and includes 21 integrated functional modules. System evaluation was conducted through End-to-End (E2E) Testing, Role-Based Access Control (RBAC) Testing, and usability assessment using the System Usability Scale (SUS) involving 30 respondents, consisting of 15 Sellers and 15 Buyers. The E2E and RBAC tests achieved a 100% success rate, while the SUS evaluation obtained an average score of 79.58, categorized as Good and exceeding the acceptable benchmark. The findings indicate that ReLapify meets usability standards and effectively addresses key challenges within the B2B ITAD ecosystem.